Annulated N‐Heterocycles by Tandem Gold(I)‐Catalyzed [3, 3]‐Rearrangement/Nazarov Reaction of Propargylic Ester Derivatives: an Experimental and Computational Study. Issue 18 (15th May 2015) - Petrović, Martina; Scarpi, Dina; Fiser, Béla; Gómez‐Bengoa, Enrique; Occhiato, Ernesto G.
Abstract: The gold(I)‐catalyzed tandem rearrangement/Nazarov reaction of propargylic ester derivatives is a useful strategy for the synthesis of cyclopenta‐fused N‐heterocyclic structures present in many natural compounds. Readily available lactams are converted into enol phosphates and triflates and coupled to propargyl alcohols under Sonogashira conditions. After acetylation, the gold‐catalyzed rearrangement of the enynyl acetates readily occurs when using 3–5 mol‐% of a gold(I) catalyst. The rearrangement generates a divinyl cation which undergoes a 4π electrocyclization (Nazarov reaction) leading to the target compound in good to excellent yield. This process has been studied in details both experimentally and computationally to understand the influence of both the reaction conditions and substrate structural features on the reaction rate and regioselectivity, as well as the torquoselectivity in the ring closure step. A series of examples illustrates at the end the scope of the reaction. Abstract : The gold(I)‐catalyzed tandem rearrangement/Nazarov reaction of suitable propargylic ester derivatives is a useful strategy for the synthesis of cyclopenta‐fused N‐heterocyclic structures present in many natural compounds. The process has been studied both experimentally and computationally in details to understand both regio‐ and torquoselectivity, and to assess its scope and limitations.